Critical factors influencing international sporting success of the Philippines : the athletes' perspective - Ramos, Ralph (2015)
The aim of this study is to contribute to the understanding of the recent declining performance of the Philippines in international sporting competitions by identifying and evaluating relevant factors that are critical to its international success through the perspective of the national elite athletes. An evaluation of the organizational effectiveness of the national sports governing bodies provides explanation to the poor performance of the country in major international competitions such as the Southeast Asian (SEA)Games.